Fibrillar form of α-synuclein-specific scFv antibody inhibits α-synuclein seeds induced aggregation and toxicity - Vijay Gupta (209146) (2020)
Synucleinopathies including Parkinson’s disease (PD), dementia with Lewy bodies (DLB), and multiple system atrophy (MSA) are characterized by pathological accumulation of α-synuclein (α-syn). Amongst the various approaches attempting to tackle the pathological features of synucleinopathies, antibody-based immunotherapy holds much promise. However, the large size of antibodies and corresponding difficulty in crossing the blood-brain barrier has limited development in this area. To overcome this issue, we engineered single-chain variable fragments (scFvs) against fibrillar α-syn, a putative disease-relevant form of α-syn. The purified scFvs showed specific activity towards α-syn fibrils and oligomers in comparison to monomers and recognized intracellular inclusions in human post-mortem brain tissue of Lewy body disease cases, but not aged controls. In vitro studies indicated scFvs inhibit the seeding of α-syn aggregation in a time-dependent manner, decreased α-syn seed-induced toxicity in a cell model of PD, and reduced the production of insoluble α-syn phosphorylated at Ser-129 (pS129-α-syn). These results suggest that our α-syn fibril-specific scFvs recognize α-syn pathology and can inhibit the aggregation of α-syn in vitro and prevent seeding-dependent toxicity. Therefore, the scFvs described here have considerable potential to be utilized towards immunotherapy in synucleinopathies and may also have applications in ante-mortem imaging modalities. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1038/s41598-020-65035-8